Using the Minority Stress Model to Understand Depression in Lesbian, Gay, Bisexual, and Transgender Individuals in Nebraska - McCarthy, M.; Fisher, Christopher; Irwin, J.; Coleman, J.; Pelster, A. (2014)
© 2014. Previous studies demonstrated the utility of the minority stress model in understanding health disparities for lesbian, gay, bisexual, and transgender (LGBT) populations. Since most research has considered large metropolitan areas, predominantly in coastal regions of the United States, this research focuses on a midwestern state, Nebraska. This study sought to assess the relationships between depressive symptoms experienced by participants (N = 770) and minority stress variables, including experiences with violence, perceptions of discrimination, and respondents’ degree of self-acceptance of their LGBT identity. Regression analysis revealed that after controlling for demographic variables, self-acceptance, and perceived discrimination were correlated with depressive symptoms. These findings have implications for policy makers, public health planners, and health care providers.